An Implementation Mechanisms of SVM Control Strategies Applied to Five Levels Cascaded Multi-Level Inverters - Mohammed Yaichi; Mohammed-Karim Fellah (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
In the area of the energy control with high voltage and power, the multilevel inverters constitute a relatively recent research orientation. The current applications of this technology are in the domains of the high voltage (over hundred kV), variable speed drives, transport and distribution of a good quality of electrical energy (HVDC, FACTS system, ....). To improve the output voltage for such inverters, many different modulation strategies have been developed. Among these strategies, the SVM (Space Vector Modulation). The technique provide the nearest switching vectors sequence to the reference vector without involving trigonometric functions and provide the additional advantages of superior harmonic quality. In this paper, we analyze different mechanisms of the output voltage synthesis and the problem of even order harmonic production. With the proposed a new trajectory SVM, which can eliminate all the even order harmonics for five levels inverter. Show clearly how to deduce the trajectories from the sequences allowing to have better performances among several possible trajectories. It is dedicated to the application of two particular trajectories.DOI: http://dx.doi.org/10.11591/ijpeds.v4i2.5507